1993
DOI: 10.1210/endo.133.2.8344189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mannose 6-phosphate receptors (MPRs) from opossum liver: opossum cation-independent MPR binds insulin-like growth factor-II.

Abstract: Bovine, human, and rat cation-independent mannose 6-phosphate receptors (CI-MPRs) are capable of binding both mannose 6-phosphate and insulin-like growth factor-II (IGF-II). However, the receptor isolated from either chicken or frog lacks the high affinity IGF-II-binding site. To determine whether CI-MPRs isolated from a species that is closely related to placental mammals can bind IGF-II, the MPRs were purified from a marsupial, the American opossum (Didelphis virginiana), by phosphomannan-Sepharose affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…It is widely hypothesized that IGF2-IGF2R binding is unique to therian mammals (marsupials and placentals) due to sexual conflict in regulating paternal IGF2 during placental and embryo development (10,(18)(19)(20)(21).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…It is widely hypothesized that IGF2-IGF2R binding is unique to therian mammals (marsupials and placentals) due to sexual conflict in regulating paternal IGF2 during placental and embryo development (10,(18)(19)(20)(21).…”
Section: Significancementioning
confidence: 99%
“…This hypothesis of mammalian-specific function was bolstered by early studies showing that IGF2R does not effectively bind IGF2 in chicken (18,21,41), Xenopus (18), or monotremes (10), and IGF2R has lower affinity for IGF2 in marsupials compared with placental mammals (19,20). However, more sensitive assays have indicated that IGF2R-IGF2 binding occurs in chicken, trout, and garden lizards (42,65,66), which counters the claim that measurable IGF2-IGF2R binding is confined to mammals.…”
Section: Members Of Iis/tor Network Are Outliers In Evolutionary Ratementioning
confidence: 99%
“…The IGFR-2 protein is encoded by an imprinted gene that diverged relatively recently (coincident with marsupialization and the evolution of the placenta) from the mannose-6-phosphate transporter -a very old gene which can be traced phylogenetically all the way back to yeast (Morgan et al 1987, MacDonald et al 1988, Clairmont & Czech 1989, Dahms et al 1993, Yandell et al 1999, Killian et al 2001b, Whyte & Munro 2001. Despite this wealth of knowledge, we know very little about how IGFR-2 is regulated.…”
Section: Introductionmentioning
confidence: 99%
“…The IGF-II/CI-MPR was purified from bovine liver by phosphomannan-Sepharose affinity chromatography as described in Dahms et al (1993). Competition for binding with 125 I-hIGF-II to bIGF-II/ CI-MPR was again expressed as a percentage of the control with no added IGF-II.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the avian and amphibian CI-MPRs lack the binding site for IGF-II but are able to bind mannose 6-phosphate-bearing ligands (Canfield & Kornfeld 1989, Clairmont & Czech 1989. However, the CI-MPR from the opossum, a species that recently diverged from placental mammals, can bind IGF-II, albeit with a 75-fold lower affinity than the bovine receptor (Dahms et al 1993). Thus, the IGF-II binding property of the CI-MPR appears to be have been acquired later in vertebrate evolution and may be limited to mammals.…”
Section: Introductionmentioning
confidence: 99%